NVP-CGM097, an HDM2 Inhibitor, Antagonizes ATP-Binding Cassette Subfamily B Member 1-Mediated Drug Resistance - Zhang, Meng; Chen, Xuan-Yu; Dong, Xing-Duo; Wang, Jing-Quan; Feng, Weiguo; Teng, Qiu-Xu; Cui, Qingbin; Li, Jing; Li, Xiang-Qi; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
Multidrug resistance (MDR) is a major challenge in the treatment of tumors. It refers to cancer cells become resistant to not only the therapeutic drug, but also cross-resistant to multiple drugs with distinct structures and mechanisms of action when they are exposed to a drug for a period of time. An essential mechanism of MDR is the aberrant expression and function of ATP-binding cassette (ABC) transporters. Therefore, blocking the function of ABC transporters has the therapeutic potential in reversing MDR. The hdm2 oncogene product, HDM2 (also known as MDM2), is an important negative regulator of the p53 tumor suppressor. NVP-CGM097 is an HDM2 inhibitor that can inhibit the proliferation of tumor cells and is currently under clinical trials. In this study, we evaluate whether NVP-CGM097 could reverse ABCB1-mediated MDR. The results of reversal experiment showed that NVP-CGM097 remarkably reversed ABCB1-mediated MDR but not ABCG2-mediated MDR. The results of Western blot and immunofluorescence suggested that the level of expression and subcellular localization of ABCB1 protein were not significantly altered by NVP-CGM097. Mechanism studies indicated that NVP-CGM097 could reverse ABCB1-mediated MDR by directly blocking the ABCB1-mediated drug efflux and raising the accumulation of chemotherapeutic drugs in cancer cells. ATPase analysis showed that low concentration NVP-CGM097 activates ABCB1 ATPase activity while high concentration NVP-CGM097 inhibited ABCB1-associated ATPase. Docking study indicated that NVP-CGM097 tended to bind to the inhibitory site, which led to slight but critical conformational changes in the transporter and reduced the ATPase activity. Overall, our study demonstrates that NVP-CGM097 can be used in conjunction with chemotherapeutic drugs to counteract MDR and improve the antitumor responses.